Kearifan Lokal Dalam Pemberdayaan Dan Pemanfaatan Tanaman Obat Keluarga (Toga) Untuk Meningkatkan Kesehatan Masyarakat (Studi Literatur) - Fitri Amja Yani; Susilawati Susilawati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Family Medicinal Plants (TOGA) are nutritious plants that are managed by the family in the yard of the house. This planting is done to provide traditional medicines that can be self-produced for family needs. This journal aims to provide an overview of how TOGA is empowered and used to improve public health in Indonesia. The writing method used in this journal is a literature review in the form of a qualitative research method. This method has characteristics in the form of text and uses secondary data by reviewing national journals through internet searches, namely Google Scholar and Researchgate whose publications have been in the last five years. Based on the results, the IEC method (communication, information, and education) and socialization is an efficient method for using TOGA. This method involves the community to participate in continuing to spread knowledge to the local community and encourages participation in the use of TOGA for daily needs which influences community empowerment and utilization. In terms of health, family medicinal plants can be used as an alternative in the treatment of common ailments, such as fever, runny nose, stomach ache, and minor injuries. The use of medicinal plants can reduce dependence on modern medicines which may be expensive or difficult to access.